2013
DOI: 10.4238/2013.october.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of L-FABP and L-BABP between fat and lean chickens

et al.

Abstract: ABSTRACT. Liver fatty acid-binding protein (L-FABP) and liver bile acid-binding protein (L-BABP), in the liver intra-cytoplasm of chicken, are members of the fatty acid-binding protein subfamily. This study was designed to analyze and compare L-FABP and L-BABP expression levels between fat and lean lines in chicken liver tissue, and to determine the relationship between their expression and lipid metabolism. Realtime polymerase chain reaction (PCR) and Western blotting were used to detect the mRNA and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In the present study, L-FABP mRNA levels of CLA-fed chickens were significantly different compared to control (P<0.05). Thus, we suggest that activation of PPAR α induced the expression of L-FABP as PPAR α is the dominant regulator of L-FABP gene in chickens (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the present study, L-FABP mRNA levels of CLA-fed chickens were significantly different compared to control (P<0.05). Thus, we suggest that activation of PPAR α induced the expression of L-FABP as PPAR α is the dominant regulator of L-FABP gene in chickens (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…Murai et al (2009) reported that L-FABP gene involved in hepatic fatty acid metabolism in chicken liver and it is influenced by several factors, including food deprivation, high-fat diets and peroxisome proliferators. L-FABP protein level is itself regulated by PPAR α transcriptional activity in chickens (Zhang et al, 2013). According to Wang et al (2006), L-FABP gene may be associated with fat traits in the chicken.…”
Section: Introductionmentioning
confidence: 99%
“…FABP2 has been identified as a specific marker for the relative amount of epithelium in humans and pigs ( 96 ). Several FABP (FABP1, FABP2, FABP6, and FABP10) have been identified to be predominantly expressed in the digestive tract of chickens ( 97 , 98 ); however, much remains to be determined regarding their expression and biological functions in poultry. FABP10 plays an important hepatic role in in response to FI in chicken ( 98 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, FABP4 may regulate abdominal fat deposition through lipolysis. Another two types of fatty acid-binding protein subfamily named L-FABP (liver fatty acid-binding protein) and liver “basic” fatty acid-binding protein (Lb-FABP) have been investigated their expression in liver between fat and lean male-chickens by Zhang et al ( 2013 ). L-FABP mRNA expression in fat birds was higher than that in lean birds at 2, 3, 4, 5, 6, and 10 weeks of age, and L-BABP mRNA expression in fat birds was higher than that in lean birds at 1, 2, 3, 4, 8, and 10 wk of age.…”
Section: Introductionmentioning
confidence: 99%